PENGARUH PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP PEMAHAMANKONSEP MATEMATIS SISWA KELAS VIII MTsN AIR BANGIS KABUPATEN PASAMAN BARAT - Yuhelmi, Yuhelmi; Rahmi, Rahmi; sovia, Anny (Pendidikan Matematika, 2014)
ABSTRACTThis research is base on the students understanding of mathematical concept are still low and studentsâ not interest in learning mathematical. This research was aimed to determine actyvity study of student and whether studentsâ understanding of mathematical concept by implementing cooperativeÂ  model type student teams achievement division better than the studentsâ understanding of mathematical concept than the implementing of conventional learning in class MTsN Air BangisÂ  school. This was an experiment research and applied random research toward the subject. Based on the perceived data analysis, the class sample has normally distributed and homogeneus. Hypothesis test result obstained = 2,00216 so the research hypothesis was accepted.Â  It can be concluded of actyvity of study point of out level from meeting first until third, and down by meeting four. And the studentâs understanding of mathematical concept by implementing cooperativeÂ  model type student teams achievement division better than the studentsâ understanding of mathematical concept than the implementing of conventional learning in class MTsN Air Bangis Â school.